STRATEGI PENGEMBANGAN USAHA PENGOLAHAN TRADISIONAL IKAN TONGKOL ASAP DI DESA JANGKAR KABUPATEN SITUBONDO - Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2014)
Research conducted in December 2012 to February 2013 in the Village Anchor, Situbondo. Stages of the research done by identifying various factors systematic review of the strengths, weaknesses, opportunities, and threats that exist in the processing units of curing and subsequent collection of primary data to the internal-external factors will be conducted through field observations. The method of analysis is done by reviewing all data collected, reducing the data and compile into elements of SWOT. SWOT matrix analysis was used to compare the strengths and weaknesses internal factors of business, as well as external factors opportunities and threats effort to obtain some alternative management strategies accordingly. The results of a study reported 4 development strategy is a top priority because it has an important role, namely: 1) Tuna smoke as exotic indigenous food require help and support from the local government and the local Office for the provision of facilities and infrastructure as well as growth capital. 2) Development of the traditional treatment of hereditary done can be indigenous product offering educational tours for visitors who come to the area Situbondo. 3) Increased and improved processing quality traditional smoked swordfish will create products that can compete with other processed products. 4) Local knowledge processing needs to be maintained and preserved.